Presenting an Evaluation Model of Digital Libraries (Iran) - Alireza Isfandyari Moghaddam; Atefeh Zarei; Elham Naiich (International Journal of Information Science and Management)
This article aimed to design and present an evaluation model of digital libraries in Iran, considering the existing and standard models in the world. It is necessary to evaluate the digital library in different design and implementation stages to achieve the predetermined goals and develop digital libraries. The development of a digital library evaluation model mainly aims to evaluate the digital library in multiple ways. It eliminates the weak points, strengthens the strong points, and provides better services in digital libraries. The current research is applied in terms of the objective and a mixed (quantitative-qualitative) type of study. Sources were identified by searching Persian and English databases, and 300 related sources were analyzed in this research. With the quantitative method, an evaluation questionnaire of digital libraries was designed, validated, and completed with the consensus of experts, and then it was sent to digital libraries for completion. The received information was entered into SPSS software. For validity and reliability, exploratory and confirmatory factor analyses and, finally, the model presentation of were done using PLS software. Based on the statistical findings of Cronbach's alpha, convergent validity, reliability coefficient, variance, standard deviation, and pebble diagrams with exploratory factor analysis by rotating the set according to the internal correlation between the items, 13 components were obtained in each element of the item, with significant correlations. On the other hand, no correlation was observed between the items of one factor and those of another. Then, the digital library evaluation model was developed in theconfirmatory factor analysis, which led to identifying 13 components (information link, architecture, information retrieval, new technologies, users, user-friendliness, applicability, information exchange, information, communication, updating, user security, and information coverage). According to the obtained findings and pattern, this pattern can be used to examine and evaluate digital libraries.